O007 ACPA-induced mobility of primed synovial fibroblasts: the missing link between ACPA-induced bone loss and synovial changes. (21st February 2018) - Sun, M; Rethi, B; Joshua, V; Krishnamurthy, A; Hensvold, A; Catrina, SB; Ospelt, C; Malmström, V; Steen, J; Engström, M; Wähämaa, H; Catrina, AI
Abstract : Introduction: Anti-citrullinated proteins antibodies (ACPAs) injected in mice induce IL-8 dependent bone loss and arthralgia, but no synovial changes. We hypothesised that additional stimuli, sensitising the synovial compartment to ACPA effects, might be needed for the transition from bone to synovial pathology. Methods: Fibroblast like synoviocytes (FLSs) were isolated from synovial tissue biopsies obtained from RA patients. Polyclonal ACPA and other non-ACPA IgGs were separated from peripheral blood of RA patients by affinity purification on protein G and cyclic citrullinated peptide (CCP)−2 columns. Monoclonal ACPAs were cloned from synovial fluid B-cells. FLS migration was tested by scratch-assays using IncuCyte (Essen bioscience). SF adhesion was analysed by xCELLigence System Real-Time Cell Analyzer (ACEA bioscience). Peptidylarginine deiminases (PAD) expression and protein citrullination were evaluated by immunohistochemistry and immunofluorescent stainings. Results: FLS mobility was not affected by polyclonal ACPA stimulation. However, exposing the cells to IL-8 or to a transient serum starvation increased PAD expression and the amount of citrullinated proteins in the cells. In line with these findings, starved FLSs obtained sensitivity to ACPAs and responded with an increased mobility to antibody stimulation. Similar effects were observed in the presence of three out of ten monoclonal ACPAs, suggesting that only APCAs with certain fine specificity could target FLSs. The ACPA-induced migration was abolished by pre-incubating the cells with PAD inhibitor or by combining the ACPAs with citrullinated but not native fibrinogen. IL-8 alone could not influence fibroblast migration but it synergistically increased the response to ACPAs. The role for inflammatory stimuli in sensitising FLSs to ACPA binding was further supported by the labelling of synovial tissues of RA patient, but not of healthy controls, using monoclonal ACPAs. Conclusions: We demonstrated that FLS response to ACPA stimulation was enabled by stress- or cytokine-induced citrullination in the cells. These results suggest an important role for transient synovial insults in setting the stage for the ACPA-mediated transition towards chronic synovitis. Disclosure of interest: None declared